2021
DOI: 10.1590/1980-549720210014.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and use of health services in the oldest old in Brazil

Abstract: Objective: To estimate the prevalence of multimorbidity in long-lived Brazilian individuals (age ≥80 years) and to associated it with the use of health services. Methods: Cross-sectional population-based study with data from the 2019 National Survey of Health (n=6,098). Frequencies of use of services were estimated for older people with multimorbidity and according to sex, health insurance ownership, and self-rated health. The prevalence rates, crude and adjusted prevalence ratios, and the respective 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
3
4
0
7
Order By: Relevance
“…In this research, it was observed that more than half of the elderly population residing in households in Brazil exhibited multimorbidity. This finding aligns with other national studies, which reported a similar proportion of 57.1% (18) . These estimates are close to those observed in high-income countries, where prevalence can reach 66.1%, indicating a high burden of this condition in the elderly population in low, middle, and high-income countries (19) .…”
Section: Discussionsupporting
confidence: 93%
“…In this research, it was observed that more than half of the elderly population residing in households in Brazil exhibited multimorbidity. This finding aligns with other national studies, which reported a similar proportion of 57.1% (18) . These estimates are close to those observed in high-income countries, where prevalence can reach 66.1%, indicating a high burden of this condition in the elderly population in low, middle, and high-income countries (19) .…”
Section: Discussionsupporting
confidence: 93%
“…11 Individuals with multimorbidity are at greater risk of receiving medical care, more frequent and longer hospital stays, polypharmacy, and a significant reduction in productivity and time off work. [12][13][14] Prospective data have shown that overweight and obesity are associated with the development of not only individual chronic conditions but also the accumulation of conditions and multimorbidity. [15][16][17][18][19] Even short-term weight gain over 3-year period has been associated with an increased risk of multimorbidity in mid-aged women, and this association was independent of baseline and time-varying BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Multimorbidity has become an emerging issue on the public health agenda of countries due to its increasing prevalence and its impact on individual health status and the financial impact on the health system 11 . Individuals with multimorbidity are at greater risk of receiving medical care, more frequent and longer hospital stays, polypharmacy, and a significant reduction in productivity and time off work 12–14 …”
Section: Introductionmentioning
confidence: 99%
“…Acreditase que a maior vinculação a um plano de saúde privado seja uma destas alternativas. 86,87,88 Sobre este aspecto, ainda que o uso combinado dos serviços públicos e privados seja uma característica do sistema de saúde brasileiro, é uma realidade que subsiste sobretudo no contexto de atenção as doenças crônicas. Acredita-se, porém, que disto resulta uma ampliação da fragmentação do cuidado já observada com estes indivíduos -múltiplas consultas de especialistas, falta de informação compartilhada, e uso inadequado da farmacoterapia e exames, entre outros procedimentos.…”
Section: Envelhecimento Da População Brasileiraunclassified
“…Acredita-se, porém, que disto resulta uma ampliação da fragmentação do cuidado já observada com estes indivíduos -múltiplas consultas de especialistas, falta de informação compartilhada, e uso inadequado da farmacoterapia e exames, entre outros procedimentos. 87,88 Assim, importante enfatizar que em um contexto em que a multimorbidade subsiste de maneira relevante entre os idosos e com impacto significativo na demanda por uso dos serviços de saúde, não apenas aumentar a oferta de cuidado representa um grande desafio para os sistemas de saúde. 53 O desafio se materializa também com a necessidade de garantir mecanismos eficientes de coordenação do cuidado nos distintos níveis e complexidades, evitando assim tratamentos concorrentes ou replicação de ações desnecessárias.…”
Section: Envelhecimento Da População Brasileiraunclassified